(372) Interpretation of quality of Linear Programming: on some Economic problems. - Eid, Moh. Sadek (The Institute Of National Planning., 2018)
Usually, linear programming problems are in the form of maximizing or minimizing an objective function under certain restrictions. such maximum and minimum problems occur frequently in many branches of pure and applied mathematics.